Comparison of Complications in Patients with Central Venous Catheter Placement Via Internal Jugular, Subclavian and Femoral Route at Intensive Care Unit: Comparison of complications of CVC placement via different routes - Haroon, Mohammad; Anwer, Ayesha (Pakistan Journal of Health Sciences, 2022)
Central venous lines are passed in almost all patients admitted in intensive care unit and a need still exist to look for best route for this purpose. Objective: To compare the complications in patients with central venous catheter passed via internal jugular, subclavian and femoral route at intensive care unit. Methods: A comparative cross-sectional study was conducted on 380 patients admitted in intensive care unit of Bahria International Hospital RWP from January 2022 to June 2022. Central venous catheters were passed by consultant critical care specialist on call at the time of reception of patient in unit. All the patients were observed for one week for presence of any local or systemic complications. Results: Out of 380 patients, 240 (63.2%) were male while 140 (36.8%) were female. Central venous catheter was passed via internal jugular vein in 220 (57.8%) patients, via subclavian route in 60 (15.8%) patients and via femoral route in 100 (26.3%) patients. Failed attempts were seen statistically significantly more in internal jugular route (p-value-0.041) while local cellulitis was seen more in femoral route (p-value-0.012). Conclusions: Internal Jugular vein was the route most commonly used for insertion of central venous catheter in patients admitted in our intensive care unit. Complications were seen more not very common in our setting. Failed attempts were more seen in internal jugular route while local cellulitis was seen more in femoral route.